Y/6-x=-1;x=-9,9

Simple and best practice solution for Y/6-x=-1;x=-9,9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y/6-x=-1;x=-9,9 equation:


750;25

(3*x-5)^3 = 0

(a^(1/3)*b^(-1/4))^-12 = 0

16.146;2.3

15/4 = 3/g

You can always share this solution

See similar equations:

| -2(18r+10)+18r=-18r-20 | | (a^(1/3)b^(-1/4))^-12 | | x-208=28 | | 15/4=3/g | | -10+12n=-4n+11+16n | | 60000/0.75 | | -40+4x=-36 | | 14k=60 | | x-322=13 | | 5x-8+40=7-x | | 3(8d+3)-19d=9+5d | | x+155=216 | | x-105=116 | | 19-3g=5g-5g-5 | | 2x+5(3x-4)(x)=3520 | | 18t-3=3(6t-1) | | 4dx+17=8d-3 | | -7/5.14 | | -19j-5=-9-19j+4 | | x-102=132 | | 11z=-15z+2(9z-8) | | 3(x+1)=12whatisx | | 3[x+2]=5[x-2] | | 75.29= | | -19b+12=-19b+18-14 | | x+3+5+x=0 | | x+41=9 | | -3n-4=-3n+1 | | 4s-1=1 | | -7u-13-3u=19-10u | | 6x-60=90 | | 8x+70=3y | | 5a-2a-5+1=-12 | | 9+17-2y=5y-16 | | 13=3(x-1)(x-8) | | $213.85(1-0.095x5/12) | | 15=37 | | 15=33 | | 5x-6x=-x | | 9w-17=-3-14+9w | | -20h+17=17-20h | | -2-2m=-18m-11+16m | | X-11/3 | | -15p+6p-8=11-9p | | 12-4x=2x-8 | | -14k-1=-14k+1 | | X+-9=14 | | r-(-17)=12 | | 6x+1y=-31 | | 6n+10=8n-8 | | 52.5-24x+1.2x^2=0 | | (2x+10)+(2x+12)=90 | | 18+5x=3(10-x) | | x^3-3x^3=0 | | -8c+10=-8c-4 | | 1/3n-2/9 | | 2v-8=10-v | | 5x+2=-3+6x | | 4x+49+2x+11=90 | | 10-m=41 | | 20x-35=65 | | 5x=50-5x | | 3.4+(3.8+j)= | | 200x+315=50x-450 | | 4.4(-5+1.1h)= |

Equations solver categories